Pengaruh Interaksi Genotipe dengan Lingkungan terhadap Kandungan Fe Biji Padi - Suwarto Suwarto; Nasrullah Nasrullah; Taryono Taryono; Endang Sulistyaningsih (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
To explore the effect of genotype, environment and genotype x environment interaction on Fe content in rice grain, Fe concentrations of 10 genotypes were analyzed across eight paddy field environments using the GGE-biplot method. Experiments were conducted from 2007 to 2008 using a randomized completely block design with three replications at each environment. Results indicated that environment (E), genotype (G) and genotype x environment interaction (GE) significantly gave effect on Fe rice concentration. Environment explained 74.43% of total (G + E + GE) variation, whereas G and GE captured 5.60% and 19.67%, respectively. The first two principal components (PC1 and PC2) were used to create a two-dimensional GGE-biplot and explained 70.40% and 15.36% of GGE sum of squares. Genotype Barumun was desirable in terms of its highest Fe rice concentration ability and stability. In Cilongok, wet season was the best representative of the overall environments and the most powerful to discriminate genotypes.